Seletividade Fisiológica de Inseticidas a Vespas Predadoras (Hymenoptera: Vespidae) de Leucoptera coffeella (Lepidoptera: Lyonetiidae) - Bacci, Leandro; Fernandes, Flávio; Picanço, Marcelo; Crespo, André; Campos, Mateus (BioAssay, 2009)
Conservation of natural enemies is an important component of integrated pest management. In this work, the selectivity of 11 insecticides used for management of Leucoptera coffeella (Guérin-Méneville) was studied to Protonectarina sylveirae (Saussure), Polybia scutellaris (White) and Protopolybia exigua (Saussure) (Hymenoptera: Vespidae). The insecticides were applied in concentrations corresponding to 50% and 100% of the field rates used for management of L. coffeella. The organophosphates (except to the 50% rate of ethion to P. scutellaris) were highly toxic to all three Vespidae species. Cartap was highly toxic to P. escutellaris and P. exigua but showed median selectivity to P. sylveirae. The pyrethroids cypermethrin, deltamethrin, betacyfluthrin, zetacypermethrin, and esfenvalerate were selective to at least one of wasp species. The mortality of P. scutelaris caused by ethion, cypermethrin, deltamethrin, betacyfluthrin and zetacypermethrin decreased when 50% of the recommended rates were used. This reduction was also observed for the mortality of P. exigua by permethrin and for the mortality of P. sylveirae by deltamethrin. P. sylveirae was the most tolerant species to cartap; P. scutellaris was the most tolerant to ethion, while P. exigua was more tolerant to pyrethroids than P. scutellaris and P. sylveirae. The results of this research indicate that pyrethroid insecticides are likely to be selective to predatory wasps in field settings given their overall selectivity in the conditions of extreme exposure of this study. The possible mechanisms underlying the selectivity of these compounds and the differential tolerance of the wasps are discussed.